Facile preparation of anodized MoO3−x films and their boosted photocatalytic activity. Issue 4 (August 2021) - Zhang, Yan; Ping, Xuecheng; Hao, Liang; He, Yiqiang; Guo, Yongkang; Zhao, Qian; Zheng, Zhaoqi; Lu, Yun
Abstract: Flexible MoO3−x films were prepared by anodic oxidation followed by annealing and liquid-phase reduction. The prepared samples were characterized by XRD, Raman spectra, SEM, UV–visible spectrophotometer, XPS, and EPR. The anodized amorphous MoO3 was transferred to the orthorhombic phase during the annealing. With the increase in annealing temperature, the MoO3 films' photocatalytic activity increased. After liquid-phase reduction, defects, including oxygen vacancies, were introduced. The defect introduction enhanced the visible light absorption and increased the charge transfer efficiency to varying degrees. Compared with the as-annealed MoO3 films, the as-reduced MoO3 films' photocatalytic activity rose by nearly four times at most. With the increase in reduction time, the bulk defect concentration increased. However, the surface defect concentration reached the maximum when the reduction time came to 2 h. The most excellent photocatalytic activity corresponded to the largest surface defect concentration, suggesting surface defects improved the photocatalytic activity. On the other hand, the bulk defects had the opposite effect. The photogenerated holes played a crucial role in the photocatalytic degradation of MB. Anodic oxidation followed by annealing and liquid-phase reduction is a facile and effective way to prepare MoO3 films with high photocatalytic activity. Graphical Abstract: ga1 Highlights: MoO3−x films were prepared by anodic oxidation followed by annealing and reduction. Liquid-phase reduction at low temperature was an effective way to introduce defects. Surface and bulk defects played opposite roles in performance improvement. Photogenerated holes played a key role in photocatalytic degradation of MB. The photocatalytic activity of the MoO3−x films was improved by four times at most.